Cool careers without college for people who love to drive - Greenberger, Robert (New York : The Rosen, 2003)
Explores the job descriptions, education and training focus on driving and do not require a college education.
Includes bibliographical references and index.
Keywords: Motor vehicle driving -- Vocational guidance. -- Juvenile literature